Genital warts and women's sexual challenges: is sexual compatibility possible? A qualitative study - Mohadese Adeli; Lida Moghaddam-Banaem; Shadab Shahali; Tahereh Soori (BMC, 2023)
Abstract Background Genital warts, besides their importance as symptoms of sexually transmitted infections, can also threaten the sexual health of couples. The purpose of this study was to explore the sexual compatibility in women with active genital warts. Methods A qualitative study with a conventional content analysis approach in Tehran, Iran, from January 2019 to February 2020 was conducted on a purposeful sample of data saturation achieved after interviewing 14 women with genital warts, 2 couples and 3 dermatologists, 1 sexologist and 1 infectious disease specialist. Data were collected through unstructured interviews and analyzed using conventional content analysis approach. Results After data analysis 224 initial codes, 5 main categories "change in the frequency of sexual activity", "changing types of sexual intercourse", "protected sexual intercourse", "concealment of lesions", "focusing on personal hygiene by couples after sexual activity" and finally a central theme of "adaptation to challenges of sexual intercourse" were extracted. Conclusions This study revealed the perceptions and experiences of women with active genital warts about the process of their sexual adaptation. The main concepts found in this study focus on challenges related to sexual intercourse. It seems that recognizing women's sexual adaptation challenges after getting genital warts may help them take effective and practical measures to improve their sexual compatibility and health.